A Triadic re-reading of Zaynab al-Ghazali and the feminist movement in Islam (2010)
This paper inquires into the personality, identity and work of the contemporary Muslim woman activist Zaynab al-Ghazali al-Jubayli (1917-2005). The quality and quantity of studies that she has attracted attest to her eminent position in both contemporary Islamic circles and feminist discourses. She has succeeded in bringing her brand of Islamic feminism to the front burners of feminist discourse at the international level. Nevertheless, there still appears to be a serious misreading of her brand of Islamic feminism. This misreading is due to the categorization of her with other Muslim women activists such as Fatima Mernissi. This paper will ground itself upon Showalter's framework which differentiates between the female, the feminist and the feminine. Also, a methodological and characteristic differentiation will be made between “Islamic feminism” and “Muslim feminism.” It is within this complete theoretical framework that this paper will discuss the life and works of Zaynab al- Ghazãli. This paper will explore the different dimensions of Zaynab al-Ghazãli’s identity, especially as a medium for the uniqueness of her brand of feminism.